Some considerations on the initiation of the present SE Ebro river drainage system: Post- or pre-Messinian? - Arche, A.; Evans, G.; Clavell, E. (Journal of Iberian Geology, 2010)
The timing and process leading to the opening of the continental Ebro Basin to the Mediterranean is a fundamental issue in the creation of the present-day drainage network of NE Iberia, yet there is no general consensus. The opening has been dated by different authors as middle Miocene to early Pliocene whilst river piracy or lake overspilling have been invoked as the geomorphic processes. Using a multiple approach to constrain the time and plausible process leading to this event, that include estimates of the age and volume of the correlative marine sediments, paleoaltitudinal reconstructions, estimates of the maximum lake level in the interior Ebro basin and rates of fluvial incision in basement rocks; it is concluded that the Ebro basin was tapped by a steep, mountain river on the E flank of the Catalan Coastal Ranges in pre-Messinian times, probably in the middle-late Tortonian.